From catching up to convergence of the latecomer firms: Comparing behavior and innovation systems of firms in Korea and the US - Buru Im; Keun Lee (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This paper addresses the issue of catching and convergence at the level of firms, and investigates whether Korean firms tend to converge toward mature firms represented by the US firms in terms of their behavior and performance as well as firm-level innovations systems. It conducts regression analyses of several behavior and performance variables, using the data of the Korean and US firms during the 1990s, the 2000s, and 2010s. It finds some evidence of convergence, such that Korean firms become more profitability- rather than growth-oriented, borrowing and investing less, and thus being less indebted. However, they have not changed much in terms of their behavior toward firm values and dividend tendencies. Further analyses, using the patent-derived, innovation system variables, also confirm some aspects of convergence, compared with the early results, for which self-citations become significant and positive for firm values; furthermore, the variable of cycle time of technology is no longer significant for profitability, which is consistent with the results from the US firms. Meanwhile, changes in corporate governance associated with the rise of foreign shareholder are also shown to have resulted in higher profitability but insignificant change in firm values. An emerging conclusion is an ongoing but partially completed process of convergence.
Keywords: 650; catch-up; convergence; innovation; Korean firms; latecomer firms; Schumpeterian; US firms